The Use of Biomedical Periodical Literature at the National Lending Library for Science and Technology - Wood, D. N.; Bower, C. A. (Methods of Information in Medicine, 1970)
The paper reports the results of a two week questionnaire survey of the use of biomedical periodical literature carried out at the UK National Lending Library in February 1969. The survey was designed to discover the subject, date and language characteristics of the borrowed literature, the most frequently requested journals, and the most popular sources of-references to biomedical publications.The loans were spread over 1,084 titles, although 9 per cent of the issues involved only 2 per cent of the titles. The literature in most demand was less than one year old and in the case of medicine 50 per cent of the requests were for literature less than 3½ years old. The half-life for the biological literature was somewhat longer at 5¾ years. The majority of issues (87.8 per cent) involved English language periodicals.Overall, the principal sources of references to the requested literature were citation lists in other periodical articles. Regarding the more recent literature, however, abstracting and indexing journals were the primary sources of information. For medical references Index Medicus was the most used indexing publication, and for biological references Current Contents.